PENGARUH LEVERAGE, CAPITAL INTENSITY RATIO DAN MANAJEMEN LABA TERHADAP AGRESIVITAS PAJAK PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2016) - Nurhayati Nurhayati; Novita Indrawati; Al Azhar A (Jurnal Ekonomi, 2018)
This study aims to find out about the influence of Leverage, Capital Intensity Ratio and Earnings Management on the tax aggressiveness of manufacturing companies in Indonesia in 2014-2016. The method used in this study is a quantitative method. The independent variables used in this study are leverage, capital intensity ratio and earnings management. While the dependent variable in this study is the corporate tax aggressiveness which is measured using the Cash Effective Tax Rate (CETR).  The population in this study is a manufacturing company listed on the Indonesia Stock Exchange (IDX) in 2014-2016, so that the total population used is 164 companies. The sampling technique used purposive sampling, namely the selection of samples according to predetermined criteria, so obtained 59 sample companies. The data used is secondary data taken through documentation techniques consisting of manufacturing company annual report 2014-2016 obtained from the Indonesia Stock Exchange data. Data analysis method in this study uses multiple linear regression with the help of software SPSS version 21. The results of this study indicate that the Leverage variable has a positive effect on the Corporate Tax Aggressivenes of 0.150. Capital Intensity Ratio variable does not negatively effect on the Corporate Tax Aggressiveness of 0.021. Earnings Management variable has a positive effect on Corporate Tax Aggressiveness of 0.253.